2021
DOI: 10.3390/pharmaceutics13020151
|View full text |Cite
|
Sign up to set email alerts
|

Study the Antifungal and Ocular Permeation of Ketoconazole from Ophthalmic Formulations Containing Trans-Ethosomes Nanoparticles

Abstract: Ketoconazole (KET), a synthetic imidazole broad-spectrum antifungal agent, is characterized by its poor aqueous solubility and high molecular weight, which might hamper its corneal permeation. The aim was to develop an ophthalmic formulation loaded with optimized trans-ethosomal vesicles to enhance KET ocular permeation, antifungal activity, rapid drug drainage, and short elimination half-life. Four formulation factors affecting the vesicles’ size, zeta potential, entrapment efficiency, and flexibility of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 54 publications
1
34
0
Order By: Relevance
“…To study effect on the minimum inhibition concentration (MIC), different dilutions of tested samples were applied. It was found that nanocapsules as drug delivery system can improve the anti-fungal activity of MN by decreasing the needed MIC from 2 µg/mL to nearly 0.75 µg/mL (Ahmed et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…To study effect on the minimum inhibition concentration (MIC), different dilutions of tested samples were applied. It was found that nanocapsules as drug delivery system can improve the anti-fungal activity of MN by decreasing the needed MIC from 2 µg/mL to nearly 0.75 µg/mL (Ahmed et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the issue of drug resistance while using a single agent remains a constrain, and combination with known antiangiogenic drugs, such as bevacizumab, could attenuate the selective pressure leading to the inhibition of angiogenesis and tumor cell death, as observed in a xenograft model of neuroblastoma ( 87 ). Moreover, nanoparticles, such as trans-ethosomes, have recently been proposed as ophthalmic formulations ( 88 ), with local noninvasive methods of treatment.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…A comparison of all liposome generation vesicles with their mechanisms and compositions is summarized in Table 2 [46][47][48]64]. For a substance to be transdermally absorbed involves some key events, given as follows [2,54,65]:…”
Section: Ultraflexible Vesicles and Ethanolic Vesiclesmentioning
confidence: 99%